2000
DOI: 10.1016/s0925-4439(99)00104-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency low-field magnetic susceptibility of ferritin and hemosiderin

Abstract: Low-frequency low-field magnetic susceptibility measurements were made on four samples of mammalian tissue iron oxide deposits. The samples comprised: (1) horse spleen ferritin; (2) dugong liver hemosiderin; (3) thalassemic human spleen ferritin; and (4) crude thalassemic human spleen hemosiderin. These samples were chosen because Mössbauer spectroscopic measurements on the samples indicated that they exemplified the variation in magnetic and mineral structure found in mammalian tissue iron oxide deposits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 24 publications
4
66
0
1
Order By: Relevance
“…In Eq. [4], V n represents the volume of the nth object and the angle brackets indicate an averaging over the object ensemble. Equation [2] is the first term of an expansion, but its precise range of validity is not, at present, rigorously known (11).…”
Section: Signal Decay Due To Strong Magnetic Field Inhomogeneitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eq. [4], V n represents the volume of the nth object and the angle brackets indicate an averaging over the object ensemble. Equation [2] is the first term of an expansion, but its precise range of validity is not, at present, rigorously known (11).…”
Section: Signal Decay Due To Strong Magnetic Field Inhomogeneitiesmentioning
confidence: 99%
“…The excess iron is primarily in the forms of ferritin and hemosiderin (2), both of which have strong magnetic properties (3,4). On a cellular scale, the iron is distributed in a highly nonuniform pattern (1,2) which results in the generation of magnetic field inhomogeneities when an external magnetic field is applied.…”
mentioning
confidence: 99%
“…In terms of the response to the magnetic field, three different classes of species were identified in the brain: The diamagnetic matrix (organic tissues, myelin, oxyhemoglobin), paramagnetic deoxyhemoglobin, paramagnetic/superparamagnetic ferritin and hemosiderin along with ferrimagnetic magnetite or maghemite [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The literature devoted to hemosiderin is strongly correlated with ferritin; however few studies on hemosiderin alone have been undertaken, 100,[173][174][175][176][177] although it is thought that hemosiderin may play an important role directly or indirectly in iron cytotoxicity and thus deserves more intensive study. The hemosiderin aggregates found in diseases might play a similar role as ferritin doses as precursors of BMNPs; however, no direct evidence for this is known.…”
Section: Hemosiderinmentioning
confidence: 99%
“…173 Hemosiderin mineral particles vary even more widely in structure than those stored in ferritin. 174 Allen et al identified three main particle structures in hemosiderin: a ferrihydrite-based structure, a highly defective structure based on goethite (α-FeOOH), and a noncrystalline Fe(III) structure. 174 The same authors found that hemosiderin particles generally have larger size distributions than particles in ferritins.…”
Section: Hemosiderinmentioning
confidence: 99%